Pengaruh Harga, Lokasi, Fasilitas Terhadap Keputusan Pembelian Membership di Ikigai Fitness Kartini - Mega Putri Lusiana Sirait; Rivera Pantro Sukma Silitonga (LPPM Universitas Asa Indonesia, 2023)
This research aims to discover how price, location, and facilities impact the decisions of Ikagai Fitness Kartini membership. The study was conducted on Ikagai Fitness customers; 109 people were taken as a random sample. This research is explanatory quantitative and uses methods such as descriptive data analysis, Several linear regression tests, classical hypothesis testing, hypothesis testing with program SPSS 25 . According to the findings, location factors had little bearing on customers' decisions to purchase memberships at Ikagai Fitness Kartini, but price and facility variables had a marginally positive and substantial impact. The study's findings demonstrate how location, pricing, and facilities affect consumer choice. to purchase an Ikagai Fitness Kartini membership.